Education of Prisoners – Between Rights and Possibilities - Knežić, Branislava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2011)
Conditions in prison (overpopulation, greyness of the space and uniforms, various deprivations, spending time with no content) are far from those needed for successful preparation for life after prison. It is more likely that success is achieved in integration into the prison environment. Education and professional habilitation are an integral part of the treatment as prescribed by the Law on execution of Penal Sanctions. The subject of this paper is to indicate the gap between the rights and possibilities of prisoners to be educated. The problem is not so much in normative solutions as in the practice of applying the prescribed solutions, as well as in the wrong perception of the role of education, training and leisure time activities in achieving the goal of prison punishment. Instead of habilitating, qualifying and requalifying prisoners by education and training for a certain profession and thus empowering them for independent living, prisons strengthen the conditions for prisoners to continue with what has brought them to prison in the first place. The success of "return rates" of prisoners to normal life in freedom, as a goal of serving the sentence, can be viewed in the context of counter education and the decrease in education. Unlawful marginalisation of education, training and skills obtaining in prisons to integrate into the real social environment creates an actual scientific and social issue of research and interest.